(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article analyzes the anti-inflammatory properties of Cinnamomum verum (cinnamon) at the molecular, biochemical, and physiological levels. It was found that cinnamaldehyde, eugenol, polyphenols, and proanthocyanidins contained in cinnamon bark reduce the secretion of proinflammatory cytokines (TNF-α, IL-1β, IL-6), inhibit the NF-κB signaling pathway, and reduce the expression of COX-2 and iNOS enzymes. The study was systematized based on the requirements of IMRAD (Introduction, Methods, Results, Discussion). The results indicate that cinnamon has pharmacological potential as a natural anti-inflammatory agent.